The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsnano.2c08275
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Nanocarriers Co-Opting Pulmonary Intravascular Leukocytes for Drug Delivery to the Injured Brain

Abstract: Ex vivo-loaded white blood cells (WBC) can transfer cargo to pathological foci in the central nervous system (CNS). Here we tested affinity ligand driven in vivo loading of WBC in order to bypass the need for ex vivo WBC manipulation. We used a mouse model of acute brain inflammation caused by local injection of tumor necrosis factor alpha (TNF-α). We intravenously injected nanoparticles targeted to intercellular adhesion molecule 1 (anti-ICAM/NP). We found that (A) at 2 h, >20% of anti-ICAM/NP were localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…This system shows promise for improved pharmacotherapy of epilepsy and potentially other CNS disorders . In another study, Nong et al demonstrated that targeting the adhesion molecule ICAM-1 enabled the transport of NPs across the BBB. They intravenously injected NPs conjugated to anti-ICAM-1 antibodies.…”
Section: Properties Affecting Nanoparticle Crossing Through the Bbbmentioning
confidence: 99%
See 1 more Smart Citation
“…This system shows promise for improved pharmacotherapy of epilepsy and potentially other CNS disorders . In another study, Nong et al demonstrated that targeting the adhesion molecule ICAM-1 enabled the transport of NPs across the BBB. They intravenously injected NPs conjugated to anti-ICAM-1 antibodies.…”
Section: Properties Affecting Nanoparticle Crossing Through the Bbbmentioning
confidence: 99%
“…Histology showed nanoparticles largely colocalized with macrophages in the brain parenchyma. In summary, targeting ICAM-1 enables leukocytes to act as Trojan horses to carry the NPs across the BBB during neuroinflammation …”
Section: Properties Affecting Nanoparticle Crossing Through the Bbbmentioning
confidence: 99%
“…There are continuing efforts for engineering targeted nucleic acid therapeutics. Pseudotyping viral vectors and virus-like particles with different surface glycoproteins have been shown to alter their tropism in vitro and in vivo . ,, Adding targeting moieties such as peptides or antibodies to lipid nanoparticles has been shown to be effective in improving their specificity of uptake to target cells. , Ongoing development of new lipids and polymers via combinatorial chemistry , for nonviral vectors and the development of directed evolution and computational design approaches for viral vectors are also expected to improve targeted delivery capabilities of these therapeutic vectors. Subcellular level targeting strategies also need to be considered since nuclear entry and integration of the nucleic acid cargo at specific genomic sites may be required for some treatment modalities …”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…The engineered nanostructures enabled the successful deployment of the COVID-19 vaccine. To safely deliver the fragile mRNA to human cells, designing novel lipid-based structures and compositions enabled RNA protection and enhanced its uptake into cells. ,,, The success of the mRNA technology during the COVID-19 pandemic inspired academics, industries, and governments to expand its therapeutic applicationsto address other infectious pathogens, personalized cancer vaccines, rare diseases, and other medically debilitating diseases.…”
mentioning
confidence: 99%
“…However, in 2005, Katalin Karikó and Drew Weissman solved this problem by modifying mRNA bases, which led to increased protein translation. They published a body of work establishing the feasibility of mRNA-based therapies. …”
mentioning
confidence: 99%